49.5k views
16 votes
Multiply:
(5x−1)(5x+4)

Multiply: (5x−1)(5x+4)-example-1
User Optimist
by
5.9k points

2 Answers

14 votes
Answer: C) 25x^2 + 15x - 4

Explanation:

To open double brackets we have to multiply each term in the first bracket with each term in the second bracket.

Therefore,
=> (5x - 1)(5x + 4)
= 5x * 5x + 5x * 4 - 1 * 5x - 1 * 4
= 25x^2 + 20x - 5x - 4
=> 25x^2 + 15x - 4
User Eric After Dark
by
6.2k points
12 votes

Answer: 25x^2+15x-4

Explanation:

Multply 5x by the other 5x

25x^2

Multiply 5x by 4

20x

Multiply -1 by 5x

-5x

Multiply -1 by 4

-4

Add them together

25x^2+20x-5x-4

Combine like terms

20x-5x=15x

25x^2+15x-4

User Kerat
by
5.8k points